Resgatando a Política Nacional de Ordenamento Territorial. Iniciativas no período de 2015 a 2021. - Cintia de Souza Alves (Confins)
This article updates the record of the Brazilian National Policy of Territorial Planning (PNOT, in Portuguese). It reports the initiatives to resume it: the transformations, advances and restrictions it has undergone in the period from 2015 to 2021. The first attempt of such a policy, in a broad sense, started in 2003, was abandoned in 2009 and remains forgotten. However, there have been recent attempts to give it a new continuity in the course of 2020 and 2021, though adverse conditions led to its drastic reduction to only one project and one pilot area. Data were collected through documentary research and, above all, from reports obtained in interviews, both with participants in the period on which this article focuses and with those involved in the previous attempt. Considering that the strategic vision for the country, the national scale and the thematic axes of territorial planning for the entire country, as well as the lack of articulation of federal policies and the way to manage them were lost since their abandonment more than a decade ago, the work of rescuing the recent experiences of formulation of a PNOT is placed here as a source for reflection and discussion; perhaps in preparation for a change of the planning and management of territorial planning in Brazil in a future phase, after 2022.